Plastic policies: Contemporary opportunities and challenges in public libraries’ enactment of cultural policy - Rivano Eckerdal, Johanna; Carlsson, Hanna (Nordic Journal of Library and Information Studies, 2022)
This study explores how democracy—often understood as an abstract concept or a location- transcending, intangible phenomenon—is produced, shaped and continuously reshaped through local library practices in certain places and under local conditions at a specific point in time. To better understand potential conflicts and/or tensions that might arise between the three levels of Swedish library policy at a time when values enshrined in the Swedish democratic model are being challenged by political right-wing populism, we explored the potential influence on and enactment of policy documents in public libraries day-to-day practice. We did so by conducting an ethnographic study of five municipalities in Sweden’s Skåne County. Our study was theoretically informed by practice theory and the view of democracy as an ongoing process and a plurality. Our findings showed that policy documents are often internalized by library staff. The influence of the democratic mission established in the Swedish Library Act , in particular, was evident in the way library staff carried out their work. One tension created by the “democratic paradox” (i.e., the requirement that a democracy allow opponents of the democratic form of rule a voice) was evident in library policy enactments, inasmuch as librarians adopted different stances towards the neutrality norm. Thus, in practice, what appear to be rigid, inflexible policy documents are in fact plastic and mouldable. This plasticity allows room for librarians to legitimately promote democracy. Although public librarians spend much time engaging with various policy documents, they consider it time well spent and value the result. Public libraries appear as locations where different levels of cultural policy interconnect. In their role as public institutions, they also have a mission to fulfil in honoring the democratic paradox via a praxis that includes support for democracy as one of their goals.